EVALUATION OF NORMAL DIAMETER OF INFRA-RENAL AORTA IN A PAKISTANI POPULATION USING CONTRAST-ENHANCED COMPUTED TOMOGRAPHY - Ullah, Sana; Imtiaz, Nauman; Ullah, Shafi; Fahad, Muhammad Shah; Nisar, Uzma; Ibrahim, Nadeem (Journal of Ayub Medical College Abbottabad, 2022)
Background: It is a common observation that the aortic size of Pakistani population is relatively less as compared to western population. Till now there is no study which has measured the dimensions of abdominal aorta in local population.The standard diameter of an artery across the body is critical for clinicians to recognize when an artery has become aneurysmal. This study aims to present the results of a local population’s normal diameter of an infrarenal aorta and how it varies by age, gender, weight, height, body mass index (BMI) and body surface area (BSA). Methods: This cross-sectional observational study was conducted in Vascular Surgery Department, at Combined Military Hospital (CMH), Peshawar, from July 2020 to November 2021.Participants in the study included all patients who underwent a contrast-enhanced computed tomography (CT) scan of the abdomen for any reason other than cardiovascular disease.The infrarenal abdominal aorta’s mean internal diameter (anteroposterior and transverse diameter) was assessed. SPSS v 23 was used to analyze the data and present it as frequency and percentages. The Pearson correlation coefficient assessed the correlation between aortic diameters, weight, height, BMI, and BSA. Result: Recruitment of a total of 250 patients was done in this study. Males were 194 (77.6%), while the rest were female patients. The patients’ mean age was 39.6±12.8 years. The mean anteroposterior (AP) diameter of the infrarenal aorta was 16.13±2.32 mm. The mean transverse diameter (TD) was 15.96±2.34 mm. The infrarenal diameter of the aorta was smaller in women when compared to men, and the calibre of the aorta increased with the increasing age of the patients. There was a statistically significant positive relationship between their age and the average diameter of the infrarenal aorta (p<0.001) among both men and women. Conclusion: Clinicians and vascular surgeons will benefit from the findings in diagnosing and treating abdominal aortic aneurysms. Hence, thoughtful consideration should be made before formulating intervention protocols.